The Thoughts of Muslim Philosopher Al Thusi on Islamic Philosophy - Nendah Mutmainah; Rabiatul Adawiyah; Fuspa Anggraeni; Wildan Muhammad taqiy; Fetty Nur Fatimah (Penerbit Hellow Pustaka, 2025)
Until now, the dynamics of thought in the Islamic filosofi world continues to grow. With an attitude that raises, is tolerant, and accommodative of Muslims to hegemony of thought as well as foreign civilization, love of knowledge, academic culture, the work of Muslim scholars in government as well as social institutions, development of schools by prioritizing ratios as well as freedom of thought, expanding the prosperity of various countries Islam, the problems faced by Islam all the time that increasingly require solutions are growing rapidly. In fact, it is possible to have a doctrine that makes reason high which may be a source of truth as well as knowledge. As for the Alquran and hadith, it is not uncommon to issue the importance of reasoning, research and thought. From this doctrine, philosophy was born in Islamic countries. With the existence of several philosophers who contributed to Islamic countries in the development of Western intellectual traditions, it turns out that many Western scientists have recognized them. Then came the philosophers in the Islamic world both in the East and West. In this paper, the character Nasiruddin At-Tusi is studied as a